Pengaruh Penggunaan Media Sosial dan Pembelajaran Kewirausahaan Terhadap Minat Berwirausaha - Sulfikar, Sulfikar; Ellyawati, Noor; Abu, Ilham (Faculty of Teacher Training and Education, Mulawarman University, 2024)
This study analyzes the influence of social media and entrepreneurship education on the entrepreneurial interest of Economics Education students at Mulawarman University. Using a descriptive method with a quantitative approach, data were collected from 100 students through questionnaires and analyzed using multiple linear regression. The results indicate that social media has a positive and significant effect on entrepreneurial interest, with a t-Count of 2.377 > t-table 1.984, and a significance value of 0.019 < 0.05. Additionally, entrepreneurship education positively and significantly affects entrepreneurial interest, with a t-Count of 6.746 > t-table 1.984, and a significance of 0.000 < 0.05. Simultaneously, the use of social media and entrepreneurship education significantly influences entrepreneurial interest, with an f- Count of 71.229 > f-table 3.09 and a significance of 0.000 < 0.05. The conclusion of this study is that both social media and entrepreneurship education, individually and together, play an important role in enhancing the entrepreneurial interest of students.